The Role of Nursing Care in the Management of Patients with Traumatic Subarachnoid Hemorrhage: Role of Nursing Care for Managements of tSAH - Miao, Qun; Yan, Yan; Zhou, Mengjie; Sun, Xueqi (Galen Medical Journal, 2022)
Traumatic subarachnoid hemorrhage (tSAH) is a critical condition that requires comprehensive management to optimize patient outcomes. Nursing care plays a key role in the overall management of patients with tSAH via various aspects of care, including neurological assessment, monitoring, intervention, and education. In this review, we aim to evaluate the significant contributions of nursing care in managing patients with tSAH. Nurses perform initial neurological assessments, including the glasgow coma scale, pupil reactivity, vital signs, and sensory-motor evaluations. These assessments provide valuable information for early identification of deteriorating neurological status and prompt intervention. Additionally, nurses closely monitor intracranial pressure (ICP), cerebral perfusion pressure, and other hemodynamic parameters, assisting in the prevention and timely detection of secondary brain injury. For example, some strategies to manage ICP include elevating the head of the bed, maintaining adequate oxygenation and ventilation, administering proper medications, and ensuring fluid and electrolyte balance. Also, through careful monitoring, early recognition, and appropriate preventive measures, nursing care could prevent complications, including infections, deep vein thrombosis, and pressure ulcers. Furthermore, nursing care extends beyond physical management and encompasses psychosocial support for patients and their families. Nurses establish therapeutic relationships, providing emotional support, education, and counseling to alleviate anxiety, address concerns, and facilitate coping mechanisms. Education regarding medication management, lifestyle modifications, and the importance of regular follow-up enhances patient compliance and promotes long-term recovery.